Top 100 most-cited articles on tau protein: a bibliometric analysis and evidence mapping - Chen, Zheping; Shan, Guoliang; Wang, Xinyue; Zuo, Yaqun; Song, Xinyu; Ma, Yufeng; Zhao, Xin; Jin, Yanwu (Frontiers in Neuroscience, 2024)
Background: Tau, a microtubule-associated protein extensively distributed within the central nervous system (CNS), exhibits close associations with various neurodegenerative disorders. Here, we aimed to conduct a qualitative and quantitative bibliometric study of the top 100 most-cited publications on tau protein and reveal the current research hotspots and future perspectives.The relevant literature was retrieved from the Web of Science Core Collection. CiteSpace(v6.2.R4) and VOSviewer (1.6.19) was adopted for bibliometric analysis with statistical and visual analysis.Results: Citations per article ranged from 615 to 3123 with a median number of 765.5 times. "Neuroscience" emerged as the most extensively researched subject in this field. The USA has emerged as the leading country, with publication record (n=65), total citations (n=66543), strong centrality (0.29) and extensive international collaborations. Harvard University (n=11) and University of California San Francisco (n=11) were the top two institutions in terms of publications. Neuron dominated with 13 articles in the 37 high-quality journals. Goedert, M from MRC Laboratory of Molecular Biology was the most productive (n=9) and top co-cited (n=179) authors. The most frequently studied keywords were Alzheimer disease (n=38). Future research is anticipated to intensify its focus on the pathogenesis of various tau-related diseases, emphasizing the phosphorylation and structural alterations of tau protein, particularly in Alzheimer's disease.The pathogenesis of various tau-related diseases, including the phosphorylation and structural alterations of the tau protein, will be the primary focus of future research, with particular emphasis on AD as a central area of investigation.